2019
DOI: 10.1103/physreva.99.012518
|View full text |Cite
|
Sign up to set email alerts
|

Variational generalized Kohn-Sham approach combining the random-phase-approximation and Green's-function methods

Abstract: A generalized Kohn-Sham (GKS) scheme which variationally minimizes the random phase approximation (RPA) ground state energy with respect to the GKS one-particle density matrix is introduced. We introduce the notion of functional-selfconsistent (FSC) schemes, which vary the oneparticle Kohn-Sham (KS) potential entering an explicitly potential-dependent exchange-correlation (XC) energy functional for a given density, and distinguish them from orbital-selfconsistent (OSC) schemes, which vary the density, or the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 106 publications
1
54
0
Order By: Relevance
“…If MP2 results are nevertheless desired, diagnostic α PT2 c values should be used to gauge their reliability. Similarly, the present results support the use of RPA calculations to calibrate dispersion-corrected DFA results.RPA calculations of NIs benefit from variational optimization of the reference,148 but the improvement appears to be most pronounced for small systems such as rare gas dimers and diminish with increasing monomer size. With average interaction energy errors consistently in the 5-10% range, RPA is accurate enough for a wide range of applications, irrespective of system size, gap size, or empirical training sets.…”
mentioning
confidence: 99%
“…If MP2 results are nevertheless desired, diagnostic α PT2 c values should be used to gauge their reliability. Similarly, the present results support the use of RPA calculations to calibrate dispersion-corrected DFA results.RPA calculations of NIs benefit from variational optimization of the reference,148 but the improvement appears to be most pronounced for small systems such as rare gas dimers and diminish with increasing monomer size. With average interaction energy errors consistently in the 5-10% range, RPA is accurate enough for a wide range of applications, irrespective of system size, gap size, or empirical training sets.…”
mentioning
confidence: 99%
“…Explorative selfconsistent spRPA calculations 60 suggested that residual density-driven errors are small. All interaction energies are counterpoise-corrected for BSSE as discussed above, and all core-orbitals were frozen in RPA correlation energy calculations.…”
mentioning
confidence: 99%
“…Taken together with the superior accuracy of RPA for large and polarizable systems without RPA calculations of NIs benefit from variational optimization of the reference, 148 but the improvement appears to be most pronounced for small systems such as rare gas dimers and diminish with increasing monomer size. With average interaction energy errors consistently in the 5-10% range, RPA is accurate enough for a wide range of applications, irrespective of system size, gap size, or empirical training sets.…”
Section: Discussionmentioning
confidence: 99%
“…The present results cast further doubt on the validity of empirical 1/R 6 corrections for very large and polarizable monomers -even though some dispersion-corrected DFAs admittedly perform remarkably well for large systems. An accurate description of NIs for such systems may require methods Similarly, the present results support the use of RPA calculations to calibrate dispersion-corrected DFA results.RPA calculations of NIs benefit from variational optimization of the reference,148 but the improvement appears to be most pronounced for small systems such as rare gas dimers and diminish with increasing monomer size. With average interaction energy errors consistently in the 5-10% range, RPA is accurate enough for a wide range of applications, irrespective…”
mentioning
confidence: 99%